Modernist art in the service of Nazi culture: Baldur von Schirach and the Junge Kunst im Deutschen Reich exhibition. (19th October 2016) - Maertz, Gregory
ABSTRACT: Maertz's essay offers a history of a modernist art exhibition that opened in Vienna's Künstlerhaus under the patronage of Baldur von Schirach, the Führer 's personal representative in that city, the second largest in Nazi Germany. The significance of the 1943 Junge Kunst im Deutschen Reich (New Art in the German Reich) exhibition lies in its assertion of a modernist variant of 'official' National Socialist art that clashes with the orthodox aesthetic system typically associated with the Third Reich.